Developing Inclusive Learning Environments : Collaborative Learning Innovations for Students with Disabilities in Higher Education - Ibnatur Husnul, Nisak Ruwah; Rusnaeni, Nani (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This research aims to develop of an inclusive learning environment for students with physical disabilities through learning innovations using collaborative learning methods. The method of research used is research and development (R&D), with the ADDIE model research design, which consists of five stages: analysis, design, development, implementation and evaluation. The population in this study were all students with physical disabilities at Pamulang University, with samples taken using a purposive sampling technique, so that representative students with physical disabilities were obtained for this research. Data was collected through interviews, questionnaires and observation methods to get a comprehensive picture of students' learning needs and experiences. The data analysis technique is carried out descriptively qualitatively, which includes needs analysis, learning design, collaborative learning video development, and evaluation of the effectiveness of the learning implemented. The results of this research show that the application of the ADDIE model in video development through collaborative learning methods succeeded in creating a more supportive learning environment for students with physical disabilities, as well as providing a more meaningful and interactive learning experience, so that student learning outcomes increased from a score of 6 to 8.